The State of Indicators of Hemostasis Parameters and Blood Parameters in Patients of the Control Group, Drugs for Prophylactic Purposes were not Administered During Cesarean Section - Akhmedov Farhod Qahramonovich; Negmatullaeva Mastura Nurullaevna (Scholars Digest Publishing, 2023)
Caesarean section (CA) (caesarean section) is a surgical operation in which the pregnant uterus is cut, the fetus and afterbirth are removed, the integrity of the uterine wall is restored. KS is one of the most common operations in obstetric practice, related to emergency aids, which should be able to be performed not only by every obstetrician-gynecologist, but also by a doctor of any specialty who owns surgical techniques. In modern obstetrics, KS is of great importance, since with a complicated course of pregnancy and childbirth, it allows you to preserve the health and life of the mother and child. CS as any surgical intervention can have adverse consequences both in the immediate postoperative period (bleeding, infection, pulmonary embolism (PE), OS embolism, peritonitis), and in the remote periods of a woman's life.
Keywords: cesarean section, pregnancy, laparotomy, bleeding.